Proses Kata Bentukan Dalam Cerpen Surat Untuk Yang Tak Akan Pernah Kembali Karya Gracellea Puehwan Limjoy - Thamrin, M.Husni; Kesuma, Ardian Ade; S, Sugiarti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to describe the word formation in the short story "Letter for those who will never return by Gracellea Puehwan Limjoy: Morphological Study". The theory used is morphology. The method used in this research is a qualitative descriptive method. The data source used is the word formation in short story "letter to those who will never return by gracellea puehwan limjoy. The data collection method used is the note-taking method. The data analysis method is the distributional method. The results of the research found the word formation. The results of the analysis concluded that there were (51) data containing elements of word formation in the form of affixes (39 words) and 12 words of repetition/repetition of words.